2011
DOI: 10.1158/1538-7445.am2011-1127
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1127: Lack of MAPK activation in significant number of uveal melanomas with somatic mutation in GNAQ and GNA11

Abstract: Purpose: The aims of this study were to investigate the correlation between MAPK activation and somatic mutation in GNAQ and GNA11 genes in uveal melanoma (UM) and to investigate the potential utility of MEK inhibition as a target for therapy of UM in tumors with GNAQ and GNA11 mutations. Methods: Sequencing and restriction fragment length polymorphism (RFLP) were utilized for detection of activating mutations in codon 209 of the GNAQ and GNA11 genes in 44 primary UMs. The expression of phospho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…However, that report was limited by studying only GNAQ codon 209 mutations and the small number of samples included 15. Our current study was conceived prior to the two clinical trials and was carried out to validate our preliminary findings that there was a lack of MAPK activation in a significant number of UM primary tumors with somatic GNAQ/11 mutations 16. In addition to confirming our earlier findings, we identified significant heterogeneity of MAPK activation within individual tumors.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…However, that report was limited by studying only GNAQ codon 209 mutations and the small number of samples included 15. Our current study was conceived prior to the two clinical trials and was carried out to validate our preliminary findings that there was a lack of MAPK activation in a significant number of UM primary tumors with somatic GNAQ/11 mutations 16. In addition to confirming our earlier findings, we identified significant heterogeneity of MAPK activation within individual tumors.…”
supporting
confidence: 81%
“…In vitro studies have shown that combinations of MAPK and PI3K pathways inhibition are more effective in controlling GNAQ mutant UM16,20 and reducing the proliferation of UM cells 14. The high frequency of AKT activation identified in our study suggests that such an approach may have a beneficial effect as well in vivo.…”
Section: Discussionmentioning
confidence: 60%